Changes in insulin sensitivity over time and associated factors in HIV-infected adolescents. (13th March 2018) - Geffner, Mitchell E.; Patel, Kunjal; Jacobson, Denise L.; Wu, Julia; Miller, Tracie L.; Hazra, Rohan; Gerschenson, Mariana; Sharma, Tanvi; Silio, Margarita; Jao, Jennifer; Takemoto, Jody K.; Van Dyke, Russell B.; et al.
Abstract : Objective: To compare prevalence of insulin resistance between perinatally HIV-infected (PHIV+) and perinatally HIV-exposed, but uninfected adolescents (PHEU), determine incidence of and contributory factors to new and resolved cases of insulin resistance in PHIV+, and evaluate glucose metabolism. Design: Cross-sectional design for comparison of prevalence among PHIV+ and PHEU. Longitudinal design for incidence and resolution of insulin resistance among PHIV+ at risk for these outcomes. Methods: The source population was adolescents from pediatric HIV clinics in the United States and Puerto Rico participating in the Pediatric HIV/AIDS Cohort Study, an ongoing prospective cohort study designed to evaluate impact of HIV infection and its treatment on multiple domains in preadolescents and adolescents. Insulin resistance was assessed by homeostatic model assessment of insulin resistance. Those with incident insulin resistance underwent 2-h oral glucose tolerance test and HbA1c. Baseline demographic, metabolic, and HIV-specific variables were evaluated for association with incident or resolved insulin resistance. Results: Unadjusted prevalence of insulin resistance in PHIV+ was 27.3 versus 34.1% in PHEU. After adjustment for Tanner stage, age, sex, and race/ethnicity, there was no significant difference between groups. Factors positively associated with developing insulin resistance included female sex, higher BMI z score, and higher waist circumference; those associated with resolving insulin resistance included male sex and lower BMI z score. Conclusion: Prevalence of insulin resistance in PHIV+ and PHEU was substantially higher than that reported in HIV-uninfected nonoverweight youth, but similar to that in HIV-uninfected obese youth. Factors associated with incident or resolved insulin resistance among PHIV+ were similar to those reported in HIV-negative obese youth. However, a contributory role of HIV infection and/or its treatment to the incident risk of insulin resistance cannot be excluded.